The relationship between the use of mobile applications (Whatsapp) and job performance at Department of Land and Survey, Kota Samarahan, Sarawak / Mardyha Mokhtar - Mokhtar, Mardyha (2018)
Mobile application (WhatsApp) has huge impact towards employee job performance. The purpose of this research is to find out the relationships between use of mobile applications and job performance at Department of Land and Survey, Kota Samarahan, Sarawak. This research use Technology Acceptance Model (TAM). The variables included in Technology Acceptance Model (TAM) are perceived usefulness perceived, ease of use and behavioural intention to use. The objectives for this study are to investigate the relationship between technology perceived usefulness, perceived ease of use, technology behavioral intention to use and job performance among the employees at Department of Land and Survey Kota Samarahan, Sarawak. This study focus at 120 supports staff. The suggested sample recommended by Krecjie and Morgan (1970) table is 96 support staffs. The results shared that technology acceptance model has strong relationship towards employee job performance at Department of Land and Survey Kota Samarahan, Sarawak because the features and design of WhatsApp is easy to use, WhatsApp can influences the behaviour towards technology and when using WhatsApp can help employee more motivated towards job performance. Hence, some recommendations and suggestion for organization, supports staff, and future researcher have been highlighted for study.